Systems thinking activities used in K-12 for up to two decades - Fisher, Diana M.; , Systems Thinking Association (Frontiers in Education, 2023)
Infusing systems thinking activities in pre-college education (grades K-12) means updating precollege education so it includes a study of many systemic behavior patterns that are ubiquitous in the real world. Systems thinking tools include those using both paper and pencil and the computer and enhance learning in the classroom making it more student-centered, more active, and allowing students to analyze problems that have been heretofore beyond the scope of K-12 classrooms. Students in primary school have used behavior over time graphs to demonstrate dynamics described in story books, like the Lorax, and created stock-flow diagrams to describe what was needed to make a garden flourish. Middle school students have created larger stock-flow diagrams to study how composting helps to reduce pollution and have created small simulations to study population dynamics and the spread of epidemics. High school students have created/used numerous computer models to study systemic problems in mathematics, physical science, physics, biology, environmental science, global studies, and history. Some high schools developed modeling courses allowing students to create System Dynamics computer models to study problems of their choice, write technical papers explaining their models, and present their models and model results to an audience. This paper contains explanations of some of the systems thinking lessons that have been used with precollege students, some for just 5–6 years (especially the primary and middle school examples), others (especially the mathematics and system dynamics model courses for high school students) for decades.